For-Profit Higher Education in Latin America: Exception or Precursor? - Salto, Dante; Levy, Daniel (International Higher Education, 2021)
Latin America leads the world in the size of legally for-profit private higher education. This reality astonishes, given three contrasting realities: The region had zero such enrollment a quarter of a century ago; its for-profit enrollment is concentrated in three countries; and the size of its total private enrollment is only a third of that of Asia. Latin America’s astonishing leap raises questions about what future for-profit private higher education might have in the vast remaining region.